Exposure to second-hand smoke is an independent risk factor of small airway dysfunction in non-smokers with chronic cough: A retrospective case-control study - Zhao, Bingrong; Bai, Lu; Wan, Rongjun; Wang, Yanan; Qin, Ling; Xiao, Qiming; Pan, Pinhua; Hu, Chengping; Jiang, Juan (Frontiers in Public Health, 2022)
Objectives This study aimed to identify the potential risk factors for small airway dysfunction (SAD) in non-smokers with chronic cough. Methods Non-smokers with chronic cough who underwent lung function tests at Xiangya Hospital from May 2019 to May 2020 were enrolled, and divided into the derivation and validation cohorts based on their hospital admission time. SAD was determined based on the presence of at least two of the following three indicators of lung function being less than 65% of predicted: maximal mid-expiratory flow, forced expiratory flow at 50% of forced vital capacity (FVC), and forced expiratory flow at 75% of FVC. Clinical data of these patients were collected. Risk factors for SAD were identified by logistic regression analysis in the derivation cohort and further confirmed in the validation cohort. Results In total, 316 patients (152 in the non-SAD group and 164 in the SAD group) were included in the derivation cohort. Compared with the non-SAD group, the SAD group had a higher proportion of female patients (82.3 vs. 59.2%, P < 0.001), was more commonly exposed to second-hand smoke (SHS) (61.6 vs. 27.6%, P < 0.001), and tended to be older (median age, 45.5 vs. 40.0 years old, P = 0.004). The median FVC, forced expiratory volume in one second (FEV1) % pred, FEV1/FVC ratio, and peak expiratory flow (PEF) % pred were slightly lower in the SAD group. Multivariable logistic analysis showed that exposure to SHS was an independent risk factor (OR 4.166 [95% CI 2.090–8.302], P < 0.001) for SAD in non-smokers with chronic cough after adjusting for related variables. In the validation cohort (n = 146), patients with SHS exposure had a relative risk of 1.976 (95% CI 1.246–3.135, P = 0.004) for SAD compared to those without SHS exposure. Multivariable logistic analysis consistently confirmed that exposure to SHS was an independent risk factor (OR 3.041 [95% CI 1.458–6.344], P = 0.003) for SAD in non-smokers. Conclusions Exposure to SHS is independently associated with a higher risk of SAD in non-smokers with chronic cough. Reduction in SHS exposure may ameliorate lung function, thus lowering the risk of irreversible airway obstruction.